2021
DOI: 10.1038/s41598-021-97093-x
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis in the adult brain functionally contributes to the maintenance of chronic neuropathic pain

Abstract: Maladaptive adult neurogenesis in the mammalian brain has been associated with diverse behaviors including disrupted learning, negative mood disorders and psychiatric conditions. However, its functional role in the generation and maintenance of chronic pathological pain has not yet been elucidated. Using an inducible genetic deletion in vivo mouse model, different behavioural paradigms and home cage monitoring systems, we show that an absence of adult neurogenesis does not impact the development of neuropathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Perhaps surprisingly, both adult neurogenesis and neuroplasticity have been reported to contribute to the maintenance of long-lasting NP (i.e., chronicity) [ 52 ] and NP that may occur adjacent to or remotely from any injury site [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps surprisingly, both adult neurogenesis and neuroplasticity have been reported to contribute to the maintenance of long-lasting NP (i.e., chronicity) [ 52 ] and NP that may occur adjacent to or remotely from any injury site [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the scope of these studies primarily focused on short‐term evaluations of cell proliferation. Due to the tightly regulated nature of the neurogenic cascade, exposure to the ischemia and other adverse environment can lead to several adverse outcomes, including increased neuroblast loss and decreased survival of newly formed mature neurons in the granular layers of the hippocampus 56,57 . In fact, it has been proposed that maladaptive neurogenesis could, in certain instances, contribute to the progression of brain dysfunction 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the tightly regulated nature of the neurogenic cascade, exposure to the ischemia and other adverse environment can lead to several adverse outcomes, including increased neuroblast loss and decreased survival of newly formed mature neurons in the granular layers of the hippocampus. 56 , 57 In fact, it has been proposed that maladaptive neurogenesis could, in certain instances, contribute to the progression of brain dysfunction. 58 Evaluating whether neurogenesis produces mature neurons and integrates into neural circuits to ameliorate behavioral deficits is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, depression is highly prevalent among patients with rheumatoid arthritis (or chronic pain), and it is also associated with poorer clinical outcomes [ 38 , 39 ]. Finally, a very recent publication demonstrated that adult hippocampal neurogenesis is involved in the maintenance of pathological pain induced by peripheral neuropathy [ 40 ].…”
Section: Introductionmentioning
confidence: 99%